Evoked cortical electrical activity associated with the presentation of a Ready-Made solution to a remote association task - I. S. Gornostaev; A. V. Kurgansky; V. K. Vyazovkina; V. F. Spiridonov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The purpose of this work was to find out which of the cortical areas, usually activated when solving insight problems, are sources of evoked activity under conditions of induced insight—insight caused by the presentation of a ready-made solution to the problem. A group of 35 adults took part in the experiment. During the experiment, the participants solved compound remote associates (CRA) task, i.e. they tried to find a word that could be used to form a word combination with three given visually presented words. A high-density EEG (128 channels) was recorded using a computer electroencephalograph (Geodesic EEG System GES 400 Series). The results of an analysis of cortical activity evoked by the presentation of a cue word in selected regions of interest are reported. These results are in agreement with what is known about the functions of the cortical areas involved in solving problems. The issue of improving the experimental technique is discussed.